2017
DOI: 10.1364/boe.8.004217
|View full text |Cite
|
Sign up to set email alerts
|

Collagen quantification in breast tissue using a 12-wavelength near infrared spectral tomography (NIRST) system

Abstract: A portable near infrared spectral tomography (NIRST) system was adapted for breast cancer detection and treatment monitoring with improved speed of acquisition for parallel 12 wavelengths of parallel frequency-domain (FD) and continuous-wavelength (CW) measurement. Using a novel gain adjustment scheme in the Photomultiplier Tube detectors (PMTs), the data acquisition time for simultaneous acquisition involving three FD and three CW wavelengths, has been reduced from 90 to 55 seconds, while signal variation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…However, the spectra for myoglobin and hemoglobin are so similar they cannot be separated in this context (Chance et al, 1988). Collagen is also an important component in bone, tendon, cartilage, muscle, and skin (Lodish et al, ) and several groups have added collagen to their fitting procedures (Pifferi et al, 2004;Zhao et al, 2017;Taroni et al, 2007;Sekar et al, 2015a;Sekar et al, 2015b).…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the spectra for myoglobin and hemoglobin are so similar they cannot be separated in this context (Chance et al, 1988). Collagen is also an important component in bone, tendon, cartilage, muscle, and skin (Lodish et al, ) and several groups have added collagen to their fitting procedures (Pifferi et al, 2004;Zhao et al, 2017;Taroni et al, 2007;Sekar et al, 2015a;Sekar et al, 2015b).…”
Section: Limitationsmentioning
confidence: 99%
“…To increase the SNR, larger area APDs or photomultiplier tubes (PMTs) could be utilized, but each of these design choices involve tradeoffs. For example, larger area APDs generally have reduced modulation bandwidth, and PMTs have limited dynamic range and linear operating regions (Zhao et al, 2017).…”
Section: Limitationsmentioning
confidence: 99%
“… 49 Collagen was not included in part because this study only took measurements up to 1000 nm, and collagen extractions have been shown to benefit from longer wavelengths, which include the absorption peaks at 1025 and 1200 nm. 17 , 50 52 Additionally, there are limited experimental methods to validate the accuracy of collagen fits. It is likely that if collagen was included as a chromophore, the lipid, water, and deoxyhemoglobin concentrations reported here would decrease to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen is also an important component in bone, tendon, cartilage, muscle, and skin, 57 and several groups have added collagen to their fitting procedures. [48][49][50]52,58 The use of collage as a contributing absorber is relatively recent, and there are limited experimental methods to validate the accuracy of collagen fits. For example, there are no known reports demonstrating the fabrication of tissue mimicking optical phantoms that incorporate collagen at physiologically relevant concentrations at the volume scales needed for diffuse optical measurements.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, larger areas APDs generally have reduced modulation bandwidth, and PMTs have limited dynamic range and linear operating regions. 58 Improvements to probe geometry and materials would also assist in measuring this patient population. For example, one subject (subject 1003) could not be measured because the tumor region was too tactile sensitive for a contact probe.…”
Section: Future Workmentioning
confidence: 99%